ORGANIZATIONAL CITIZENSHIP BEHAVIOR DAN KINERJA AKADEMIS MAHASISWA - Budi Gautama Siregar (IAIN Padangsidimpuan, 2018)
OCB is formally defined as behavior above and beyond of the role that is described formally with the role of organizational, natural freedom, and it is not rewarded directly or explicitly in the context of the structure of the formal recognition of the organization, and it is importance for the effectiveness of implementation and critical success of an organization. OCB is also importance for the provision of students’ business and career business who is similar with the successfull of the organization in the future, the scale which is students engage in these behaviors , it will be investigated directly in academic determination. Involvement of students with OCB will provide benefits that can be shown in a future career of students’ succesfull. This is the responsibility of lecturers in business field to inform students about the important of OCB and instruct them in using their applications. Students who do OCB should be encouraged by educators to purify and further develop their skills